Bangladesh : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on the National Strategy for Accelerated Poverty Reduction for Bangladesh. The paper discusses that accelerating growth and bringing a pro-poor orientation in the growth process would be achieved through emphasizing four priority areas: accelerated growth in rural areas and development of agriculture and nonfarm economic activities; small and medium manufacturing enterprises; rural electrification, roads, water supply and sanitation; and information and communication technologies. Moreover, there are critical follow-up issues, which will determine the success of the poverty reduction strategy.